Polar and dipolar contributions to collective cell motility - Zhang, G (2022)

(untitled)
Active materials take energy from their surroundings and use it to do mechanical work. The theories of active matter can describe a wide variety of living systems, such as bacterial colonies, actin-myosin networks and cell tissues. In this thesis, we investigate the collective behaviour of confluent, two-dimensional cell monolayers on a substrate, which is also one of the most common experimental systems to study collective cell motility. The cells are modelled using a computational phase field approach to study how polar and dipolar forces, the active, out-of-equilibrium force components, contribute to the cell motions.